PENILAIAN INDIKATOR KESEHATAN HUTAN RAKYAT PADA BEBERAPA POLA TANAM (Studi kasus di Desa Buana Sakti, Kecamatan Batang Hari, Kabupaten Lampung Timur) - Deya Puspa Ansori; Rahmat Safe’i; Hari Kaskoyo (PERENNIAL, 2020)
Awareness of the importance of community forest health in various cropping patterns in Buana Sakti Village, Batang Hari District, East Lampung Regency is currently lacking, so better forest management is needed. Community forest has a function as a forest that can support community income. This study aims to obtain the value of community forest health indicators on monoculture, polyculture, and agroforestry cropping patterns. This research was conducted in a community forest in Buana Sakti Village, Batang Hari District, East Lampung Regency. This study uses the FHM (Forest Health Monitoring) method. The results showed that the indicators of community forest health used in monoculture planting patterns were productivity, vitality, location quality. In the polyculture planting patterns, namely productivity, vitality, site quality and biodiversity. Indicators used in agroforestry cropping patterns are productivity, vitality, site quality, and biodiversity.